THE ESTABLISHMENT OF SHAYBANID RULE IN MAWARANNAHR - B. N. Sirojov (Modern American Journals, 2025)
At the turn of the 16th century, the Timurid empire in Mawarannahr (Transoxiana) faced a terminal crisis of political legitimacy and structural integrity, creating a significant power vacuum.
Keywords: Transoxiana, Timurid decline, Uzbeks, Appanage system, Central Asia.